Pomalidomide in Patients with Interstitial Lung Disease due to Systemic Sclerosis: A Phase II, Multicenter, Randomized, Double-blind, Placebo-controlled, Parallel-group Study - Hsu, Vivien M.; Denton, Christopher P.; Domsic, Robyn T.; Furst, Daniel E.; Rischmueller, Maureen; Stanislav, Marina; Steen, Virginia D.; Distler, Jörg; Korish, Shimon; Cooper, Alyse; Choi, Suktae; Schafer, Peter H.; et al. (Journal of Rheumatology, 2017)
To evaluate the safety and efficacy of pomalidomide (POM) on forced vital capacity (FVC), modified Rodnan skin score (mRSS), and gastrointestinal (GI) symptomatology over 52 weeks of treatment in patients with interstitial lung disease due to systemic sclerosis (SSc).Twenty-three adult patients diagnosed with SSc were randomized 1:1 POM:placebo (PBO).Mean change at Week 52 from baseline in predicted FVC% -5.2 and -2.8; mRSS -2.7 and -3.7; and UCLA Scleroderma Clinical Trial Consortium Gastrointestinal Tract (SCTC GIT 2.0) score 0.1 and 0.0, with POM and PBO, respectively. Statistical significance was not achieved for any of these 3 primary endpoints at 52 weeks.Because of recruitment challenges, subject enrollment was discontinued early. In an interim analysis, the study did not meet its Week 52 primary endpoints. Therefore, a decision was made to terminate all study phases. POM was generally well tolerated, with an adverse event profile consistent with the known safety and tolerability profile of POM in other diseases. Study results were neither positive nor negative because too few subjects were enrolled to make meaningful conclusions. Clinical Trials number: NCT01559129.
EVALuna2:13459